Adaptive Line Resistance Estimation and Compensation for Accurate Power Sharing of Droop-Controlled DC Microgrids - Xiangyu Qin; Zhengyu Lin; Wei Jiang; Hazel Lee (Energies)
For a DC microgrid with a traditional droop control strategy, achieving accurate power sharing among power converters is challenging due to mismatched line resistance. In a multi-bus DC microgrid system, changes in the power flow can further lead to variation in the equivalent line resistance of each power converter. To improve power sharing accuracy, an adaptive line resistance estimation method is proposed in this paper, which can accurately estimate line resistance without additional hardware. The estimated line resistances are then used to compensate the droop coefficient of each power converter to ensure accurate power sharing between power converters. Simulation and experimental results are presented to demonstrate the effectiveness of the proposed method for single bus, multi-bus, and ring-bus DC microgrid systems.